TI_GERICHTE 52.2019.286 vom 7. Mai 2019 , Tassa di soggiorno - parità di trattamento e ammontare delle tariffe - TI Tribunale d'appello (2019)
Tassa di soggiorno - parità di trattamento e ammontare delle tariffe